2022
DOI: 10.26803/ijlter.21.7.9
|View full text |Cite
|
Sign up to set email alerts
|

“I Can Teach With My Videos”: How Do Teachers Teach English to Young Learners in a Technology-Limited Environment?

Abstract: To ensure that learning continues during the Covid-19 pandemic, educators must understand pedagogical and content knowledge through the integration of information and communication technology (ICT). An example is English teachers at elementary schools in Indonesia making videos to help young learners learn English remotely. This paper aims to find out how teachers maximize student learning from their videos in a technology-limited environment and how teachers integrate their role as facilitators into their vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In doing so, young learners will have great opportunities for interactive lessons. In addition, teachers of young learners are seen as facilitators in such a technological environment (Astutik et al, 2022). Hence, this paper investigates Jordanian EFL teachers' knowledge and perceptions of word identification improvement through using IWB technology.…”
Section: Word Identificationmentioning
confidence: 99%
“…In doing so, young learners will have great opportunities for interactive lessons. In addition, teachers of young learners are seen as facilitators in such a technological environment (Astutik et al, 2022). Hence, this paper investigates Jordanian EFL teachers' knowledge and perceptions of word identification improvement through using IWB technology.…”
Section: Word Identificationmentioning
confidence: 99%
“…Hence, instructors must comprehend pedagogical and material knowledge through the integration of information and communication technologies in order to ensure that learning continues during the COVID-19 pandemic (Astutik & Setiawan, 2022). According to Nguyen (2015), about 92 per cent of all distance and online education studies have concluded that distance and online education are at least as successful as traditional education, if not more so.…”
Section: The Covid-19 Pandemic and The Use Of Technology In Educationmentioning
confidence: 99%
“…The integration of technology, including interactive educational apps, digital storybooks, and online learning platforms, can motivate young learners and offer engaging content and interactive exercises (Tiftik, 2021;Taghizadeh & Yourdshahi, 2020;Saffold, 2021;Astutik et al, 2022;Harahap & Kembaren, 2023;Perez et al, 2021). When technology is selected and integrated appropriately, it can enhance engagement and provide opportunities for independent practice.…”
Section: Technology-assisted Learningmentioning
confidence: 99%